PERMEABILITAS BETON DENGAN PENAMBAHAN STYROFOAM - Ketut Sudipta, I Gusti; Sudarsana, Ketut (Jurnal Ilmiah Teknik Sipil, 2009)
The purpose of this research is to investigate the relationship between coefficient permeability of concrete and volume of granular styrofoam added into a concrete mix. The styrofoam added to concrete is in order to have concrete with a smaller density. The concrete was mixed using Portland cement type I, sand from Karangasem which was proportioned to meet zone 2 of gradation limit, gravels from the same source as sands which was also proportioned to meet gradation limit with maximum diameter of 25 mm according to ASTM C 33-74 and round granular styrofoam with diameter ranges from 3 mm to 10 mm having density of 22,89 kg/m3. Concrete mix was proportioned according to the ingrediens weight that is 1:2:3, respectively for cement, sand and gravels with water cement ratio of 0.5. Variation of the styrofoam added into the concrete mix is 0%, 10%, 20%, 30%, and 40% of total mix volume. The specimens used in this experiment is standard concrete cylinders with diameter of 150 mm and 300 mm in height. The specimen was tested at 28 days of age. The experimental results show that the coefficient of concrete permeability increases with increasing additional granular styrofoam into the concrete mix. The coeficient of permeability is 2,274x10-9 cm/dt; 4,170x10-9 cm/dt; 7,917x10-9 cm/dt; 17,839x10-9 cm/dt; and 42,135x10-9 cm/dt for addition of styrofoam 0%, 10%, 20%, 30%, and 40%, respectively. The relationship between the coeficient of permeability and percentage of styrofoam added into the concrete follows a nonlinear regresión curve.
Keywords: Permeability, styrofoam, concrete